PENGARUH KEBIJAKAN SPIN-OFF, BEBAN OPERASIONAL PENDAPATAN OPERASIONAL (BOPO), DANA PIHAK KETIGA (DPK), DAN NON PERFORMING FINANCING (NPF) TERHADAP PROFITABILITAS PERBANKAN SYARIAH DI INDONESIA - Sihombing, Novri Hasian; Yahya, M. Rizal (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
The purpose of this study is to examine the effect of independent variables on profitability of islamic banking in indonesia for the period of 2008 to 2015. Independent variables used in this study are spin-off policy, operating expense to operating income (OEOI), third party fund, and non performing financing (NPF). The method that used for this study is purposive sampling, from 12 islamic banking in indonesia, 6 islamic banking are choosed as the sample in this study. The type of data used in this study is secondary which is financial statement. Collecting data technique used in this study is documentary.Data is analyzed by statistical analysis using a multiple regression analysis. The data is processed by IBM Statistical Package for Social Science (SPSS) 20th version program. The result of the study show that 48,7% dependent variable or profitability ratio can be explained by the four of independent variables. Silmutaneously the four of independent variables have effect on profitabilit. Individually spin-off policy and third party fund have not effect on profitability. Meanwhile, operating expense to operating income varibles have effect significant on profitability.Keywords: profitability, spin-off policy, operating expense to operating income, third party fund, non performing financing, islamic bank.